Metyrapone for Long-Term Medical Management of Cushing’s Syndrome - Andrea N. Traina; Ashley Farr; Ritu Malik; Robert J. Bingham (Case Reports in Endocrinology)
Cushing’s syndrome is characterized by any cause of excess cortisol in the blood and produces many physiologic consequences. Left untreated, Cushing’s is associated with significant morbidity and mortality. Seventy percent of endogenous cases of Cushing’s syndrome are secondary to a pituitary tumor; because of this, the primary mode of management is surgical resection of the tumor. Should hypercortisolism persist following surgical resection, further treatment options are limited. Metyrapone is an orphan medication that is often used in the diagnosis of the disease and occasionally for short-term treatment prior to surgery. Long-term treatment with metyrapone is usually discouraged due to the contradictory increase in ACTH production, acne, hirsutism, hyperkalemia, edema, and other mineralocorticoid effects. We present a patient with refractory Cushing’s syndrome successfully treated for nearly 6 years with metyrapone with minimal adverse effects. This orphan medication may be a viable long-term treatment option for this difficult disease.